KOMUNIKASI PERSUASIF DUTA LINGKUNGAN DALAM MENINGKATKAN GAYA HIDUP RAMAH LINGKUNGAN PADA PROGRAM KAMPUNG IKLIM BADAN LINGKUNGAN HIDUP KOTA PEKANBARU - Sherly Luciana; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Kampung Iklim’s program is the national program developed by the Ministry of Environment to encourage the active participation of the community and all the parties in implementing local action. The action to increase the resilience to climate hange and redution of green house gas emissions. Through the implementation of this program, the government rewards the communities in specific locations which are already implementing mitigation and adaption to climate change sustainably. In execute Kampung Iklim’s program, the environment ambassador using persuasive communication to those public by way of encouragement and the example in implementing eco-friendly lifestyle. This research aims to determine the credibility of the persuader, persuasive message and the effets produed by the environment ambassador in promoting eco friendly lifestyle.This researh using qualitative research method with descriptive approah. The subject of this research was choosing by purposive technique who consist of BLH, environment ambassador, society who are joined in climate village. Data was collected through interview, observation and documentation. Data was analyst using interative model of Miles and Huberman. To achieve the validity of the data in this study, researcher used the triangulation technique.The tehnique showed that environmental ambassador have credibility as communiator that is expetness in a way socialization and have knowledge about the environment and trust worthiness that is environmental ambassador apply eco-friendly lifestyle. A persuasive message used consists of verbal message, include clarity, directness, and auray. While nonverbal message with give example eco-friendly lifestyle like bring a tumblr and use handkerchief and utilization seondhand like used beverage bottles and old paint bucket into flower pot and water media for hydroponic. The resulting efffect, first is an inrease, knowledge, comprehension and awareness on people’s self about environment of information provided by environmental ambassador. Second, eonomic that is sense of public concern felt by citizen. Third, culture that is action which is conducted by citizen for eco-friendly lifestyle.Keyword: Environment Ambassador, Eco-Friendly Lifestyle, Kampung Iklim.